The Indonesian Islamic Student Association's Idea About Civil Society - Nasution, Faiz Albar; Nasution, Nabila Fahira (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Students have an important role in the political system, because they have their own place for society. Students have four roles, namely agent of change, social control, iron stock, and moral force. To make citizens aware of their role, a student organization is needed as a real form of student forum so that they can explore their potential and abilities, achieve missions with one purpose of the organization. Commitment in the organization, as well as the knowledge base is able to build a student's frame of mind, so that he hopes to answer the problems that occur in society. One of the issues that is often discussed is building the concept of civil society in Indonesia. As a student organization, the Islamic Student Association based on Islam is able to assess civil society based on an integral understanding of Islam. The purpose of this service is to provide an understanding of the Indonesian Islamic Student Association's Ideas for Civil Society during the activities of the introduction of prospective members of the Islamic Student Association. The results of the service from this activity are: First, providing understanding and knowledge about the Indonesian idea of Islamic student associations to civil society. Second, interactive discussion between participants and presenters. Third, the presenter becomes the carrier of the discussion flow by solving problems.